Microstructure Evolution and Performance of AA2024 Alloy Through Wire-Arc Additive Manufacturing Under Different Heat Inputs - Jin Yang; Aimin Wang (Metals)
Wire-arc additive manufacturing (WAAM) is widely applied in the aerospace, automotive, defense, and other industries. As such, the study of the formation and evolution mechanism of grains to achieve precise control over the performance of additive parts is important. In this study, AA2024 high-strength Al alloy wire was used to produce WAAM specimens under different heat inputs by varying different parameters. Subsequently, their microstructure, phases, and tensile properties were analyzed. The results indicated that the predominant crystal comprised cellular crystals, columnar crystals and dendritic crystals. At a heat input of 5500–6200 kJ m−1, the internal morphology of the specimen, characterized by the significant presence of fine cellular crystals, was predominantly favorable. As the heat input increased, α (Al) and θ (CuAl2) phases were increasingly identified within the specimens, the grid-like distribution of the θ phase along the crystal boundaries became clearer, and the θ′ phase precipitation decreased. Solution treatment and aging of the specimen produced using the optimal WAAM parameters resulted in an ultimate tensile strength (UTS) of 398 MPa, yield strength (YS) of 284 MPa, and elongation of 11.3%. The results should serve as a basis for selecting suitable WAAM process parameters.